Are Leaders and Managers with High Emotional Intelligence Superior Performers? - Hosie, Peter; Sharma, A.; Willemyns, M.; Herkenhoff, L. (ANZAM, 2012)
Leaders and managers with high emotional intelligence are often argued to be high job performers.Evidence from the literature is used here to examine the veracity of this claim. Emotional intelligencewas found to be a necessary but not sufficient precondition for improving individual leader andmanagers’ job performance and ultimately organisational productivity. EI is best most appropriatelyconceived of in terms of the abilities concerning the recognition and regulation of emotion in the selfand others. Organisational culture needs to support the application of EI competencies and rewardmanagers and leaders who exhibit socio-economic competencies for this proposition to be supported.